Technology Integration and Teacher Collaboration as a Strategy for Improving Islamic Religious Education Competence - Muh Nasir, Tatang; Wulan, Sri; Sugiana, Yusuf; Badrudin, Badrudin; Nursobah, Asep; Sadiah, Dewi (Journal of Leadership, Management and Policy in Education, 2026)
This study aims to identify and analyze effective strategies for improving the competency of Islamic Religious Education (PAI) teachers through a continuous professional development program. PAI teacher competency plays a crucial role in shaping the character and religious values of students. However, challenges in implementing relevant development programs are still encountered, especially in the era of digital change and the demands of 21st-century education. This study used a qualitative approach with a case study method conducted at SMPN 1 Kadipaten, Tasikmalaya Regency. Data were collected through in-depth interviews, observations, and documentation studies, which were then analyzed thematically. The results showed that effective competency development strategies at the research site included several main aspects, namely: (1) technology-based training for the creation of innovative teaching media; (2) collaboration between teachers through the Teacher Working Group (KKG) and Subject Teacher Consultation (MGMP) forums; (3) intensive coaching through academic supervision by the principal and supervisor; and (4) providing constructive and continuous feedback. The active involvement of the principal and support from the education supervisor proved to be key factors in creating an environment that supports continuous learning for PAI teachers. In conclusion, a planned and structured professional development program, as implemented at SMPN 1 Kadipaten, is able to significantly improve the pedagogical and professional competence of Islamic Education teachers.